The Domestic Environment and Respiratory Health of School Children in Zongshan, China. (November 2014) - Spickett, Jeffery; Rumchev, Krassi; Jing, He
There have been many reports on the adverse impacts of exposures to particulate matter in the air but relatively few of these have been related to exposures to ultrafine particles (UFP) in the indoor environment. To investigate exposures to (UFP) in domestic environments, and the association with childhood respiratory symptoms in Zongshan, China a modified Thoracic Society questionnaire was completed by 359 households with children. Air quality monitoring took place in 37 households using a P-Trak instrument to determine concentration of UFPs in rooms. The mean number of UFP was 4.1 × 10 4 cm −3 . A range of factors was found to be associated with UFP concentration and self-reported childhood respiratory symptoms. In conclusion, the evidence suggests that behavioural and environmental factors contribute to increased UFP concentrations indoors although there was no statistically signification correlation between indoor ultrafine particle concentration and any reported repeated episodes of respiratory symptoms.